Waste management of shrimp farms as starting point to develop integrated farming systems (case study: Kuwaru Coast, Bantul, Yogyakarta, Indonesia) - Saiya, H G; Katoppo, D R (Journal of Degraded and Mining Lands Management, 2015)
Intensive waste management is a solution to maintain an area of ecological harmony but still can produce economic benefits that are beneficial to social welfare. So in this research, waste of shrimp farms which was just processed by using zeolite, was treated again with a few treatments, i.e. simple filters, constructed wetlands, shell, fish and composting. Simple filters were composed of stone, gravel, coral, charcoal, sand and coconut fibers. Constructed wetland system used was hybrid type which combines type of horizontal flow and type of vertical flow. The shell used was Polymesoda erosa. The fish used was Tilapia. In the composting sediment activator, biang kompos was used with the composting time of one month. The results indicated that the system ofsimple filters, constructed wetlands, shells and fish proved to be quite effective to reduce levels of pollutants in wastewater and will be more effective if treatment was accompanied with a proper aeration. While, the sediment composted into fertilizer needed to be composted with a longer time than normal composting time. This was because the composted materials were derived from wastehaving a very low nutrient, so it took longer to restore nutrients. The results also indicated the potential of shrimp farm waste of PT. IBD to be processed into clean water and fertilizer. With the appropriate policies and strategies, this can lead to the development of an integrated farming system to support sustainable coastal ecologically, economically and socially.